2014
DOI: 10.1016/j.compscitech.2014.05.034
|View full text |Cite
|
Sign up to set email alerts
|

Controlling and mapping interfacial stress transfer in fragmented hybrid carbon fibre–carbon nanotube composites

Abstract: DESCRIPTION.Composites Science and Technology publishes refereed original articles on the fundamental and applied science of engineering composites. The focus of this journal is on polymeric matrix composites with reinforcements/fillers ranging from nano-to macro-scale. CSTE encourages manuscripts reporting unique, innovative contributions to the physics, chemistry, materials science and applied mechanics aspects of advanced composites.Besides traditional fiber reinforced composites, novel composites with sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The limitation of using graphene nanoplatelets as strain sensors can be clearly seen in Figure . On one hand, its strain sensitivity can be limited by the relatively small aspect ratio of the platelets compared with previous research focused on SWNTs with high aspect ratios, , although this may be partially compensated by further improving the interaction between fiber surfaces and graphene through the usage of a more appropriate coating solution and functionalization of graphene. On the other hand, since each graphene flake acted like an individual strain sensor and the variation in their dimensions as well as chemical composition for EG graphene resulted in different strain sensitivities for each flake, the strain reported by graphene flakes will be scattered as shown in Figure .…”
Section: Resultsmentioning
confidence: 97%
“…The limitation of using graphene nanoplatelets as strain sensors can be clearly seen in Figure . On one hand, its strain sensitivity can be limited by the relatively small aspect ratio of the platelets compared with previous research focused on SWNTs with high aspect ratios, , although this may be partially compensated by further improving the interaction between fiber surfaces and graphene through the usage of a more appropriate coating solution and functionalization of graphene. On the other hand, since each graphene flake acted like an individual strain sensor and the variation in their dimensions as well as chemical composition for EG graphene resulted in different strain sensitivities for each flake, the strain reported by graphene flakes will be scattered as shown in Figure .…”
Section: Resultsmentioning
confidence: 97%
“…Tailoring or "architecting" the material in relation to both its structural and non-structural services is an inherent ability of advanced composites and is rapidly emerging technology for their next generation. Understanding their mechanical behavior requires the study of the interface, the common physicochemical areas between the distinct phases (reinforcing and matrix materials) [1,2]. This is a prerequisite for the design of a composite material, as its behavior is most of the times governed by its interfacial properties [3].…”
Section: Introductionmentioning
confidence: 99%
“…Even though the deformation of individual carbon nanotubes cannot be followed via the application of strain in combination with Raman spectroscopy as a result of their nanoscale dimensions, they can be used as coatings of different types of fibres and the local stress can then be studied by using Raman spectroscopy. The works of Jin et al 257,258 revealed that the coating of low-and high-modulus carbon fibres with carboxylated SWCNTs enabled them to analyse the fibre fragmentation during the deformation process and to follow the 2D Raman band shifts along the fibre length. The presence of the SWCNTs led to very high interfacial shear stress, in the order of 50 MPa and >30 MPa for low-and high-modulus carbon fibres, respectively, as a result of the additional bonding caused by the presence of the functional groups.…”
Section: Cnt-based Compositesmentioning
confidence: 99%